Transparansi Pemberian Insentif Pajak Pertambahan Nilai Ditanggung Pemerintah Pada Sewa Toko di Mal - Noor Eva Rahma (Jurist-Diction, 2022)
AbstractThe COVID-19 pandemic has affected and changed the system of order in almost all aspects of world life, including the economic aspect. The Ministry of Finance currently has three focuses, namely providing funding for the health sector, providing social protection for the community, and supporting the business world as outlined in the National Economic Recovery (PEN) program. Based on Article 3 of Law No. 9 of 2020 concerning the State Budget for the 2021 Fiscal Year, tax revenues are planned to contribute Rp. 1,444 trillion, or 82.8% of the 2021 APBN target of Rp. 1,743 trillion. One of the government's efforts to support PEN is to provide incentives for Government Borne Value Added Tax, which is given for room rentals carried out by retail traders as regulated in PMK No. 102/PMK.010/21 concerning VAT on the Delivery of Room or Building Rental Services to Retail Traders Borne by the Government for the 2021 Fiscal Year. Problems arise when the PMK does not explain it in detail.Keywords: Tax Incentives; Value Added Tax; Room Rent. AbstrakPandemi Covid-19 telah mempengaruhi dan mengubah sistem tatanan hampir seluruh aspek kehidupan dunia, tidak terkecuali aspek ekonomi. Fokus Kementerian Keuangan saat ini ada tiga, yaitu penyediaan pendanaan sektor kesehatan, pemberian perlindungan sosial untuk masyarakat serta dukungan kepada dunia usaha yang dituangkan dalam program Pemulihan Ekonomi Nasional (PEN). Berdasarkan Pasal 3 UU No. 9 Tahun 2020 tentang APBN Tahun Anggaran 2021, penerimaan pajak direncanakan dapat menyumbang sebesar Rp1.444 triliun atau 82,8% dari target APBN 2021 sebesar Rp1.743 triliun. Salah satu usaha pemerintah untuk mendukung PEN adalah memberikan insentif Pajak Pertambahan Nilai Ditanggung Pemerintah yang diberikan atas sewa ruangan yang dilakukan oleh pedagang eceran yang diatur dalam PMK No. 102/PMK.010/2021 tentang PPN atas Penyerahan Jasa Sewa Ruangan atau Bangunan kepada Pedagang Eceran yang Ditanggung Pemerintah tahun Anggaran 2021. Permasalahan timbul ketika PMK tersebut tidak menjelaskan secara rinci. Kata Kunci: Insentif Pajak; Pajak Pertambahan Nilai; Sewa Ruangan.